Influence of the structure on the capillary suction of the micro concrete - TOUKOUROU, CHAKIROU A.; BAGAN, GONTRAND COMLAN; VAUTRIN, Alain (My University, 2014)
The micro concrete is a variable water and cement aggregate mix, following quite precise standards. It is an extremely fragile, but very significant heterogeneous material for the implementation of the tiles and the plates in many countries. The aim of the study was to investigate the influence of the microstructure of the micro concrete on its capacity of suction. The results showed that the capacity of suction decreased with the increase in the coarse sand rate of the cementing matrix.
Keywords: Micro concrete; brittle material; porosity; hydrous absorption power